2021
DOI: 10.3389/fonc.2021.672677
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Tumor Mutation Burden: Tumor Neoantigen Burden as a Biomarker for Immunotherapy and Other Types of Therapy

Abstract: Immunotherapy has significantly improved the clinical outcome of patients with cancer. However, the immune response rate varies greatly, possibly due to lack of effective biomarkers that can be used to distinguish responders from non-responders. Recently, clinical studies have associated high tumor neoantigen burden (TNB) with improved outcomes in patients treated with immunotherapy. Therefore, TNB has emerged as a biomarker for immunotherapy and other types of therapy. In the present review, the potential app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 106 publications
(98 reference statements)
1
43
0
Order By: Relevance
“…However, because of the low toxicity of immunotherapy, the exploration of immunotherapy approaches for WT has never stopped. 35 , 38 Therefore, it was hoped that our study could bring some ideas for the follow‐up research of WT.…”
Section: Discussionmentioning
confidence: 96%
“…However, because of the low toxicity of immunotherapy, the exploration of immunotherapy approaches for WT has never stopped. 35 , 38 Therefore, it was hoped that our study could bring some ideas for the follow‐up research of WT.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, using the somatic mutation data available in the TCGA cohort, we found obviously lower TMB in the high-risk group. It has been reported that tumors with low TMB generates fewer neoantigens, thus avoiding being attacked by CTLs ( Wang et al, 2021b ). Taken together, these findings suggested the important role of IRLPS in determining TME cell infiltration and predicting response to ICB therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that tumor mutation burden (TMB) has emerged as a promising biomarker for predicting the immunotherapeutic response, we also calculated the TMB of GC patients in the TCGA cohort. TMB was defined as the total number of nonsynonymous mutations per megabase in the coding area of a tumor genome ( Wang et al, 2021b ). The “maftools” and “GenVisR” R packages were used to analyze and visualize common mutations ( Skidmore et al, 2016 ; Mayakonda et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Increased neoantigen load renders the tumor immunogenic with increased infiltration of lymphocytes leading to better clinical response to ICI in non-small cell lung cancer, melanoma, colorectal adenocarcinoma ( 185 ). In a breast cancer model, recent research from our group found that tumor hypoxia increased tumor mutational load and potential neoantigens ( 186 ).…”
Section: The Hidden Potential Of Hypoxia-modulated Genetic Heterogene...mentioning
confidence: 99%